Pengaruh Adopsi Teknologi Budidaya Padi terhadap Produktivitas Padi di Sumatera Selatan - Irfansyah, Muhammad; Wildayana, Elisa; Yamin, Muhammad (Jurnal Social Economic of Agriculture, 2024)
The implementation of cultivation paddy technology is important to be carried out on food crop commodities to support food availability in Indonesia. This study has purpose to analyze the adoption rate of rice cultivation technology and its productivity in rainfed and tidal land, and to analyze the comparison of rice farming productivity in rainfed and tidal land. This research is located in Lubuk Seberuk Village, Ogan Komering Ilir Regency for the typology of rainfed land and Upang Jaya Village, Banyuasin Regency for the typology of tidal land. The research method used in this study is a survey method and a sample drawing method using a stratified random sample with a total of 90 respondents. The data used in this study are primary and secondary data. The results show that there is a significant difference between the productivity of the two typologies of rain-fed land and tidal land. The T-test analysis showed that there was a significant difference between productivity in rainfed land and tidal.